IOP-lowering and neuroprotective treatment for glaucoma: reality and prospects - A.E. Egorov; N.G. Glazko; A.B. Movsisyan (РМЖ "Клиническая офтальмология")
A.E. Egorov1,2, N.G. Glazko2,3, A.B. Movsisyan1,2 1Hospital for Disabled Veterans No. 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3City Clinical Hospital No. 15, Moscow, Russian Federation Glaucoma is one of the most common chronic ocular disorders which results in irreversible eye damage. This paper summarizes the data on key aspects of glaucoma pathogenesis accumulated in the recent decades. It was demonstrated that elevated intraocular pressure (IOP) is still an important and well-studied risk factor for vision loss in both open-angle and angle-closure glaucoma. Management algorithms for glaucoma which consider disease progression include three major principles, i.e., IOP lowering to achieve target IOP, maintenance and improvement of ocular blood flow, and neural retinal protection. Currently, prostaglandin analogues and their combinations are considered the most effective IOP-lowering agents. Medications which contribute to the contraction of trabecular meshwork and regulation of aqueous humor outflow have demonstrated their efficacy in different phases of clinical trials. They should be adopted in the immediate future. In addition, novel drug delivery strategies are developed. Therefore, the aim of pathogenically-based treatment using modern therapeutic agents is to save maximum vision and the quality of life in most patients. Keywords: primary open-angle glaucoma, intraocular pressure, glaucomatous optic neuropathy, neural retinal protection, IOP-lowering treatment, prostaglandin analogues, carbonic anhydrase inhibitors, beta blockers, alpha-2 agonists, prostamides, fixed-dose combinations.  For citation: Egorov A.E., Glazko N.G., Movsisyan A.B. IOP-lowering and neuroprotective treatment for glaucoma: reality and prospects. Russian Journal of Clinical Ophthalmology. 2019;19(3):128–135. About the authors: 1,2Alexey E. Egorov — MD, PhD, Professor, Professor of A.P. Nesterov Department of Ophthalmology, Head of the Department of Ophthalmology, ORCID iD 0000-0003-2637-1830; 2,3Nadezhda G. Glazko — MD, postgraduate student of A.P. Nesterov Department of Ophthalmology, ophthalmologist, ORCID iD 0000-0002-1175-3695; 1,2Anna B. Movsisyan — MD, postgraduate student of A.P. Nesterov Department of Ophthalmology, ophthalmologist, ORCID iD 0000-0001-8233-0385. 1Hospital for Disabled Veterans No. 2. 168, Volgogradskiy av., Moscow, 109472, Russian Federation. 2N.I. Pirogov Russian National Research Medical University. 1, Ostrovityanova str., Moscow, 117997, Russian Federation. 3City Clinical Hospital No. 15. 23, Veshnyakovskaya str., Moscow, 111539, Russian Federation. Contact information: Alexey E. Egorov, e-mail: alexeye@inbox.ru. Financial Disclosure: no authors has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 14.04.2019.